Attitude of Piggery Entrepreneurs of Pashu-Vigyan Incubator towards Scientific Pig Farming - Anna, Akriti; Singh, Braj Pal; Chander, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Pig farming is gaining momentum as a promising source of unconventional livestock farming in the current global scenario in which the food habits of Indian consumers is changing. It is one of the untapped livestock sectors, attracting entrepreneurs from all dimensions, searching for a great profit-generating source of livelihood, fetching sustainable returns if managed on scientific lines. Under the RKVYRAFTAAR scheme of the Government of India, the Agribusiness Incubation Center (ABIC) of ICAR-Indian Veterinary Research Institute (IVRI), also called Pashu-Vigyan Incubator is continuously organizing the piggery Entrepreneurship Development Programme (EDP) to popularize pig farming in India. The present paper, based on ex-post-facto research conducted at IVRI enlightens the atmosphere around scientific pig farming. It ascertains the attitude of the trainees towards scientific pig farming and the EDP as a whole. A purposive sampling technique selected 80 trainees who positively started their piggery enterprises after attending the EDPs at Pashu-Vigyan Incubator IVRI Izatnagar. The data collection was done through e-questionnaires and telephonic follow-up. Majority of the trainees agreed that the ‘government should organize training for scientific piggery management’, believed that ‘cross bred animal is a symbol of progressiveness’ and ‘looked forward to adopting scientific piggery practices’. Almost half of them held ‘favourable’ attitude towards piggery entrepreneurship, followed by 42% who held ‘more favourable’ attitude towards the same.